Stand-up Comedy as an Interartistic Genre in Contemporary Literature - Ahmad Razi; Mobina Abedi (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
Stand-up Comedy is a type of audio-visual art that has received serious attention in recent decades. It is a combination of verbal and dramatic arts derived from Oral literature and deeply ingrained in folk culture. Stand-up comedy encompasses different forms of art and performance such as storytelling, acting, music, presenting and oration. Comedians engage with the audience directly on stage, regaling them with amusing anecdotes about life and societal matters, inducing laughter and providing a mental release. The findings of this survey indicate that owing to the distinctive features of stand-up comedy, this form of art will gain significant popularity in future. This particular form of contemporary art serves various purposes including, entertainment, education, creating social solidarity and empathy, as well as critiquing political and societal issues. Its notable interartistic features encompass storytelling, being audience's oriented, being critical, improvisational, flexibility, and drawing on informal language and colloquialisms. The present article explores the history of stand-up comedy in Iran, its functions, its structure and defining characteristics. Additionally, the article delves into the significant themes, elements, styles, and techniques employed by comedians in crafting their performances, and three cases of Iranian performances are analyzed as examples.